Strategi Bisnis Terintegrasi Secara Online untuk Meningkatkan Penjualan di Era Digital di Indonesia - Aqila Tamima; Djurmiani Nasution; Nur hazizah; Mhd. Arifta Pulung Tumangger; Nur baiti (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This research aims to learn more about online Integrated Business Strategies in the Digital Age. With the rapid development of technology, new media have emerged which are closely related to the internet. Which is where the internet is now a necessity for many people around the world because it allows them to quickly and easily find the information they need. The Internet made inroads into the world of business, creating new changes. Fields of online business today that are growing rapidly include the fashion and styling sector, the furniture sector, and also the electronics sector. The Fashionable field is a very high field because many people follow the flashlight trend. One of them is product marketing. With the development of the times, now many people choose to buy and sell online. This is because online is easier and cheaper. Oneway toincrease online sales is by means of promotion, because promotion is the most important thing in developing the online business that we live in. With the promotion of the business that we live can be seen or heard by other people in various directions. The research method used is qualitative by distributing questionnaires fordata processing and using previous theoretical references to make it more significant. The purpose of this research is to link the organizational functions of various systems and process data processing from various platforms to be more effective. In addition, the integrity system can also reduce business operational costs. The results of this study include several interrelationships of an effective and efficient business system. In addition, business integrity has many benefits, especially for online businesses to make their business growin today's digital era. Keywords: Online Business, Digital Era, Promotion